Penerapan Media Pembelajaran E-Comic Dalam Meningkatkan Pemecahan Masalah Matematis Siswa - Rezky, Sri; Surya, Edi; Fauzi, Kms. Muhammad Amin (Pusdikra Publishing, 2024)
The aim of this research is to determine the development of e-comic learning media to improve the mathematics problem solving abilities of 4th grade elementary school students. The type of research carried out uses descriptive qualitative with field research methods. The type of research used is Research and Development with a 4-D design which includes a modification of the Thiagarajan model (1974:36). The stages carried out in 4-D design are the definition stage, design stage, development stage by carrying out validation tests on material, media and learning experts. After the results of the e-comics media development material test, media expert test and learning expert test were categorized as valid and feasible. Then the final stage is carried out, namely the distribution stage which aims to promote e-comic media to teachers and students. So it can be concluded that the development of e-comics media is suitable for application in mathematics learning to improve students' mathematical problem solving abilities.